The insupportable validity of mosquito subspecies (Diptera: Culicidae) and their exclusion from culicid classification - Harbach, Ralph E.; Wilkerson, Richard C. (Zootaxa, 2023)
Beginning about 80 years ago, the recognition of morphological varieties of mosquitoes was gradually replaced by the recognition of subspecies. As an examination of revisionary and detailed taxonomic studies of mosquitoes clearly shows, subspecies are untenable concepts which have been synonymized with nominotypical forms or recognized as distinct species. Thus, from our perspective, subspecies is not a functional or practical taxonomic rank. Consequently, in this study we critically assessed the taxonomic status of the 120 nominal taxa distinguished as subspecies before now to determine whether they should be recognized as separate species or synonymous names. As a result, 96 subspecies are formally elevated to specific rank, 22 are relegated to synonymy with nominotypical forms, one is considered a nomen dubium, one a species inquirenda and the names of four nominal species regarded as synonyms are revalidated. The subspecies and their new status are listed in a conspectus. The revalidated species include Anopheles argentinus (Brèthes, 1912), from synonymy with An. pseudopunctipennis Theobald, 1901c; An. peruvianus Tamayo, 1907, from synonymy with An. pseudopunctipennis as nomen dubium; Culex major Edwards, 1935, from synonymy with Cx. annulioris consimilis Newstead, 1907; and Trichoprosopon trichorryes (Dyar & Knab, 1907), from synonymy with Tr. compressum Lutz, 1905. Additionally, the type locality of Anopheles sergentii Theobald, 1907 is restricted to El Outaya, Biskra Province, Algeria. A complete list of species to be retained, added to or removed from the Encyclopedia of Life, with a few corrections, is provided.